KONTRIBUSI WAKAF DALAM PENANGGULANGAN KEMISKINAN - Suaidi (Journal of Innovation Research and Knowledge, 2022)
Waqf as a type of worship related to property aims for social purposes. According to Islamic law, the qualifications of a person's good or bad depend on his concern for others, the higher the concern for others, the higher the level of iman (believe). As stated by Allah in the holy Quran: You will never achieve righteousness until you donate some of what you cherish. And whatever you give is certainly well known to Allah. (Q.S. Ali-Imran: 92). However, many muslims still live in poverty in various aspects, inability to fulfill daily needs and the need for a decent place to live, where many Muslims are still homeless living under bridges and some even use sidewalks as a place to live, a place to rest after a long day of begging. This phenomenon is actually a concern of Muslims in an effort to overcome poverty by realizing Islamic law which is oriented to poverty alleviation. Among them is the waqf system which has legal force in accordance with Law No. 41 of 2004, that waqf is a legal act to give some of our property to be used forever or for a certain period of time according to his interests for the purposes of worship and/or general welfare according to sharia. Thus, if waqf is carried out properly, it will be able to improve people's welfare and overcome poverty.